DIGOXIN DOSE EVALUATION ON HEART FAILURE PATIENTS WITH RENAL DISFUNCTION IN RSUP DR. SARDJITO, YOGYAKARTA - Jhonson P Sihombing; Lukman Hakim; AM Wara Kusharwanti (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2017)
Digoxin is a medicine with narrow therapeutic index. Digoxin is widely used for heart failure treatment. Adjustment of digoxin dose is needed in patient with renal dysfunction. This research were done to evaluate digoxin dose in heart failure patient with renal dysfunction. This research was retrospective and prospective research, performed in Dr. Sardjito hospital during January 2010 to March 2011. Data were collected from patient medical record and then evaluated with descriptive method. From 43 patients, percentage men compare to women were 56 % : 44 %. Most patients come from age of 50 – 59 (34.88%). Dose calculation based on pharmacokinetic concept found that some of digoxin dose in patients were exceed digoxin therapeutic concentration. From 19 women patients there were 11 patients use digoxin dose exceed digoxin therapeutic concentration when calculate by pharmacokinetic while from 24 men patients there were 14 patients use digoxin dose exceed digoxin therapeutic concentration when calculate by pharmacokinetic. Dose recalculation method was mostly based on literature data particularly for pharmacokinetic parameter values i.e. volume distribution, half life, and clearance. Therefore, the corrected doses suggested in this thesis should be regarded as theoretical estimates. Furthermore, it was also found that patients did not get appropriate loading dose of digoxin. However, drug dosing for digoxin were individual dose, therefore overall found that patient clinical outcome was generally better. Keywords : digoxin, heart failure, renal dysfunction, clinical outcome